IMPLEMENTASI MEDIA SIKEFA (SISTEM KELIPATAN DAN FAKTOR) DALAM PEMBELAJARAN MATEMATIKA DI MI BUSTANUL ULUM SEBANI - Fatchiyah Rahman; Edy Setiyo Utomo; Wiwin Sri Hidayati; M. Aliyur Rohman Hidayat; Dewi Masithoh; Nabila Nur Aina (JP-MAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the quality of mathematics learning at MI Bustanul Ulum Sebani through the implementation of the SIKEFA (Sistem Kelipatan dan Faktor) learning media. Based on observations, it was found that fifth-grade students had difficulty understanding the concepts of LCM (Least Common Multiple) and GCF (Greatest Common Factor) because learning was still dominated by lecture methods that were abstract and less interactive. SIKEFA media was developed as a modification of the traditional mancala game adapted into the context of mathematics learning. The implementation method consisted of three stages: preparation (coordination, needs analysis, learning tool preparation), implementation (media introduction, collaborative learning, observation), and evaluation (pre-test, post-test, satisfaction questionnaire, reflection with the teacher). The results showed an increase in the average student score from 35.23 (pre-test) to 54.38 (post-test), with an average student satisfaction score of 81.54. In addition to improved conceptual understanding, students also showed increased activeness, confidence, and learning motivation. SIKEFA media proved effective as a concrete, enjoyable, and meaningful learning alternative, with potential for further development for other mathematics topics.